(untitled) (Polis (Santiago), 2018)
The term “governance”, which has become a buzzword lately, alludes to horizontal and participative modalities in management as opposed to the traditional model of a centralized and interventionist state. This phenomenon takes place in a context of intensified globalization and international interconnection, “debt crisis”, increase in extreme poverty in the South, rise of mafias, environmental crises, world insecurity and unprecedented humanitarian disasters. Together with this, we witness a liberal attack against the welfare state under accusations of inefficiency, protectionism and corruption. However, the so called “minimal state” usually brings about an agravation of pre-existent evils: social exclusion and disintegration, endemic unemployment, increasing insecurity and lack of protection of vast sectors of the population.